Clinical features of patients with MOG-IgG associated disorders and analysis of the relationship between fibrinogen-to-albumin ratio and the severity at disease onset - Li, Yue; Wang, Sai; Liu, Panpan; Ma, Jinxiu; Liu, Xinjing; Yuan, Jing (Frontiers in Neurology, 2023)
Objective The study aimed to investigate the differences in clinical features between pediatric and adult patients with first-episode MOG-IgG associated disorders (MOGAD) and evaluate the relationship between the fibrinogen-to-albumin ratio (FAR) and the severity of neurological deficits at disease onset. Methods We retrospectively collected and analyzed biochemical test results, imaging characteristics, clinical manifestations, expanded disability status scale (EDSS) score, and FAR. The Spearman correlation analysis and logistic regression models were used to examine the association between FAR and severity. Receiver operating characteristic (ROC) curve analysis was to analyze the predictive ability of FAR for the severity of neurological deficits. Results Fever (50.0%), headache (36.1%), and blurred vision (27.8%) were the most common clinical manifestations in the pediatric group (<18 years old). However, in the adult group (≥18 years old), the most common symptoms were blurred vision (45.7%), paralysis (37.0%), and paresthesia (32.6%). Fever was more common in the pediatric group, while paresthesia was more common in the adult patients, with all differences statistically significant (P < 0.05). The most frequent clinical phenotype in the pediatric group was acute disseminated encephalomyelitis (ADEM; 41.7%), whereas optic neuritis (ON; 32.6%) and transverse myelitis (TM; 26.1%) were more common in the adult group. The differences in clinical phenotype between the two groups were statistically significant (P < 0.05). In both pediatric and adult patients, cortical/subcortical and brainstem lesions were the most common lesions on cranial magnetic resonance imaging (MRI), whereas, for spinal MRI, cervical and thoracic spinal cord lesions were the most commonly observed. According to binary logistic regression analysis, FAR was an independent risk factor for the severity of neurological deficits (odds ratio = 1.717; 95% confidence interval = 1.191–2.477; P = 0.004). FAR (r = 0.359, P = 0.001) was positively correlated with the initial EDSS score. The area under the ROC curve was 0.749. Conclusion The current study found age-dependent phenotypes in MOGAD patients as ADEM was more commonly observed in patients < 18 years old, while ON and TM were more frequently found in patients ≥18 years old. A high FAR level was an independent indicator for more severe neurological deficits at disease onset in patients with a first episode of MOGAD.